PEMBERDAYAAN KONSUMEN CERDAS: EDUKASI MEMILIH PRODUK PANGAN UMKM KERUPUK LAPIS YANG AMAN DAN BEBAS PEWARNA MAKANAN SINTETIS - Novriyanti Lubis (LPPM Universitas Abdurrab, 2026)
Food safety is an important aspect of protecting public health, particularly in food products produced by Micro, Small, and Medium Enterprises (UMKM). The misuse of prohibited synthetic food colorants remains a concern due to their potential adverse effects on consumer health. This community service activity aimed to educate consumers and UMKM producers on the importance of selecting safe food products and understanding the risks associated with synthetic food colorants. The program was conducted through industrial visits, direct observation of the production process, educational counseling, questionnaire distribution, and evaluation of respondents’ knowledge regarding food safety. A total of 30 respondents participated in the survey. The results showed that 56.7% of respondents believed that the layered crackers were produced using natural food colorants, while 16.7% assumed that synthetic colorants were used. Furthermore, 73.3% of respondents understood the concept of food safety, and 80% were aware of the dangers associated with prohibited synthetic food colorants. However, consumer consideration of hygiene aspects during food production remained relatively low. The educational activities contributed positively to improving public awareness and knowledge regarding food safety and encouraged consumers to make more informed choices when selecting food products. In conclusion, the program successfully enhanced respondents’ understanding of food safety and the potential health risks associated with prohibited synthetic food colorants. Continuous education is necessary to support the development of informed consumers and to encourage UMKM to maintain the safety and quality of their products